Integrating circular economy into business models : A study on B2B plastic products manufacturers and international customers - Benedetta, Urbani (My University, 2024)
Environmental issues have increasingly become a matter of concern for the general public and sustainability has emerged as a central topic for both producers and consumers. Therefore, industrial companies are pressured to innovate at business model level and integrate sustainability. A possible solution is the circular economy (CE), a “closed loop system” that is built on sustainable practices and its primary objective is to enhance resource efficiency and minimize waste by effectively managing materials and energy cycles. The adoption of CE principles and practices leads to circular business models (CBM). The existent literature does not analyse the transformation process that companies undergo to implement CBMs and how this transformation generates value, economic advantages and revenue at company level. Consequently, there is a need to deepen the understanding of how sustainability, in particular the environmental dimension, can be integrated in business models and used to create value for customers in international contexts. This thesis focuses on the plastic industry, in particular on business-to-business (B2B) plastic products manufacturers operating internationally. The aim of the research is to answer the following question: “How do B2B plastic products manufacturers incorporate circular economy approaches into their business models to improve the value perception and willingness to pay of their international customers?”. The objective is to explore how this type of companies, despite operating with plastic, a material often associated with pollution, are able to successfully implement circular business models and create customer value by leveraging environmental sustainability. The research is conducted as a qualitative multi case study. It considers three companies operating in the moulding of low-value plastic products and packaging industry. These companies are headquartered in Italy but operate with customers all over the world.The data is collected through five semi-structured interviews and by analysing companies’ websites and sustainability reports. The results indicate that B2B companies producing plastic products are gradually moving towards CBMs but they are facing many trade-offs which slow down the transition. The main CE practices adopted include substituting virgin raw materials with recycled ones and energy efficiency improvements. Companies aim at a CBM because it entails efficiency and reduced waste, allowing cost savings. However, at the same time, working with recycled materials involves higher production costs due to technical features. Customers are starting to value sustainability, especially in Europe, but they still prioritise characteristics such as quality of the product, delivery times and mostly the price. From the interviews it is clear that at the end customers still look at the price. Consequently, the adoption of circular economy practices does not always correspond to an increase in the willingness to pay of customers. They often demand sustainable products due to legal requirements and therefore are not willing to voluntarily pay a premium price. Therefore, it is fundamental the role of institutions which economically incentivise companies by providing the necessary funds for a transition.
Keywords: circular economy; business models; value creation; willingness to pay; business-to-business commerce; plastic products; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business